THE METHODICAL ASPECTS OF MAXIMA USING AS A TOOL FOR FUNDAMENTAL TRAINING OF BACHELORS OF COMPUTER SCIENCE (Journal of Information Technologies in Education (ITE), 2015)
Within the formation of the information society, where the pace of scientific progress is rapidly growing, it is difficult to provide the training for immediate inclusion of the person into the production chain at a workplace or in an educational system. There is the way out and it is fundamentalization of informatics education. It is necessary to train the specialist so that he (she) could be able to be adapted quickly to the changes occurring in the industry technological development; to give him knowledge, universal in nature, so as the expert may navigate quickly to resolve the professional tasks on this basis.     The article describes the trends of systems of computer mathematics (SCM) pedagogical use for teaching computer science disciplines. The general characteristics and conditions for effective use of the Maxima as a tool for fundamentalization of the bachelors learning process are outlined.The ways of informatics disciplines teaching methodology are revealed. The peculiarities of cloud based learning solutions are considered.      The purpose of the article is the analysis of contemporary approaches to the use of systems of computer mathematics as a tool for fundamentalization of informatics disciplines training courses and identify methodological aspects of these systems application for the teaching of operations research as by the example of SCM Maxima.     The object of investigation is the learning process of informatics bachelors with the use of SCM.     The subject of investigation is the peculiarities of using the SCM Maxima as a learning tool for informatics courses support
Keywords: bachelor of computer science; informatics disciplines; computer mathematics system; Maxima; graph model; cloud technology